Relationship between Blood Lead Levels and Anemia: A Cross-Sectional Study on Mining Workers from Peru - Bertha Pumallanqui-Ramirez; Jair Li; Lenin Rueda-Torres; Jaime Rosales-Rimache (Hindawi Limited, 2024)
Background. Lead exposure is an environmental and occupational health problem associated with different clinical outcomes; however, its relationship with anemia in mining workers is not well characterized. This study evaluated the relationship between blood lead level (BLL) and anemia in mining workers who underwent annual medical-occupational evaluations. Methods. We conducted a cross-sectional study to estimate the association between the BLL and anemia in workers of a mining company during the year 2019. We obtained occupational information and laboratory test results, with the hemoglobin level for identifying anemia and BLL measured by atomic absorption spectrophotometry. The relationship between BLL and anemia was evaluated in a generalized linear model with a log link and the Poisson family to obtain crude and adjusted prevalence ratio (aPR) and its 95% confidence intervals (95% CIs). Results. Three hundred forty mining workers, mainly male (95%), with a mean age of 36.8 ± 9.4 years, were evaluated. The median hemoglobin and BLL were 14.1 g/dL (Interquartile range (IQR): 13.0-15.3) and 3.4 µg/dL (IQR: 2.1−4.8). Only one worker presented a BLL exceeding the upper limit value established by the Ministry of Health of Peru (up to 40.0 µg/dL). We found anemia in 21.8% of the mining workers (CI95%: 17.5-26.5). A low and inverse correlation between hemoglobin and BLL (rho: −0.169) was obtained in this study. BLLs were significantly associated with anemia (aPR: 1.04; 95% CI: 1.01-1.08). Conclusion. Occupational exposure to lead is weakly associated with anemia in mining company workers. Strengthening actions to prevent and control lead exposure is relevant and guarantees the comprehensive promotion of worker health and healthy workplaces.